2018
DOI: 10.1111/jerd.12418
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of minimally invasive coronally advanced flap and modified coronally advanced flap for the management of multiple adjacent gingival recession defects: A split mouth randomized control trial

Abstract: Introduction Various minimally invasive surgical approaches are proposed for the management of gingival recession. A modified surgical approach coined as minimally invasive coronally advanced flap (MICAF) was compared with modified coronally advanced flap (MCAF) for the management of multiple adjacent gingival recession defects. Materials and methods Seven systemically healthy subjects with bilateral multiple adjacent maxillary facial gingival recession defects (Miller I) were included in this study. In each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 14 publications
4
17
0
3
Order By: Relevance
“…In the present study in both groups the parameters of PD, CAL, GRD and GRW exhibited reduction in values at both the time points of 6 and 12 months with the Test group indicating greater reductions than the Control group. Amongst these parameters, the more relevant from the patient's point of view were the GRD and GRW as they are clinically noticeable and are directly reflective on the aesthetic component during function.The above findings are somewhat similar to those reported by Rajendran et al10 wherein the authors compared minimally invasive coronally advanced flap with the modified coronally advanced flap and secured a difference of 2.22 ± 0.17 mm of GRD and 3.05 ± 0.49 mm between the baseline and 6 months postoperative measurements. Although the difference of these parameters achieved in the present study seems to be less at 1.29 ± 0.69 mm and 0.98 ± 0.30 mm for Test and Control groups respectively, however, the reason for this is the fact that above referenced study included only Millers class I defects only while in the present study RT1 defects were included.…”
supporting
confidence: 89%
“…In the present study in both groups the parameters of PD, CAL, GRD and GRW exhibited reduction in values at both the time points of 6 and 12 months with the Test group indicating greater reductions than the Control group. Amongst these parameters, the more relevant from the patient's point of view were the GRD and GRW as they are clinically noticeable and are directly reflective on the aesthetic component during function.The above findings are somewhat similar to those reported by Rajendran et al10 wherein the authors compared minimally invasive coronally advanced flap with the modified coronally advanced flap and secured a difference of 2.22 ± 0.17 mm of GRD and 3.05 ± 0.49 mm between the baseline and 6 months postoperative measurements. Although the difference of these parameters achieved in the present study seems to be less at 1.29 ± 0.69 mm and 0.98 ± 0.30 mm for Test and Control groups respectively, however, the reason for this is the fact that above referenced study included only Millers class I defects only while in the present study RT1 defects were included.…”
supporting
confidence: 89%
“…The 318 included papers reported studies carried out in 46 different countries and published between 2018 and 2020. The total number of patients included ranged from 7 (Rajendran et al 2018) to 1877 (Ramsay et al 2018). A total of 62 papers (19.5%) were published in journals with IF < 1, 213 papers (66.9%) in journals with IF 1-4 and 43 papers (13.5%) in journals with IF > 4. study design was clearly reported in the paper, and how study design was interpreted by the reviewers (if not reported).…”
Section: Re Sultsmentioning
confidence: 99%
“…Dessa forma, diversas técnicas cirúrgicas foram propostas para o tratamento das RGs, podendo estar ou não associadas ao ETCS e/ou biomateriais. A técnica de ACR têm sido uma das técnicas mais estudadas para o tratamento das RGs, sendo que evidências cientificas mostram que o ACR isolado promove resultados satisfatórios de redução da recessão gengival (RRG) (RAJENDRAN, et al, 2018;CAIRO, et al, 2017). , et al,2009).…”
Section: Classificação E Tratamento Das Recessões Gengivaisunclassified
“…Outros estudos na literatura corroboram com a percepção de 1mm como a diferença clínica mínima entre grupos (MCGUIRE & SCHEYER, 2010;RAJENDRAN, 2018).…”
Section: Quantidade De Anestésicos Medicação Pós-operatória E Tempo D...unclassified
See 1 more Smart Citation